Moisture-Resistant Scalable Ambient-Air Crystallization of Perovskite Films via Self-Buffered Molecular Migration Strategy - Yang, Mei; Zhu, Weidong; Liang, Laijun; Chai, Wenming; Wu, Xiaomeng; Ren, Zeyang; Zhou, Long; Chen, Dazheng; Xi, He; Zhang, Chunfu; Zhang, Jincheng; Hao, Yue (Nano-Micro Letters, 2025)
Ambient-air, moisture-assisted annealing is widely used in fabricating perovskite solar cells (PSCs). However, the inherent sensitivity of perovskite intermediate-phase to moisture—due to fast and spontaneous intermolecular exchange reaction—requires strict control of ambient humidity and immediate thermal annealing treatment, raising manufacturing costs and causing fast nucleation of perovskite films. We report herein a self-buffered molecular migration strategy to slow down the intermolecular exchange reaction by introducing a n–butylammonium bromide shielding layer, which limits moisture diffusion into intermediate-phase film. This further endows the notably wide nucleation time and humidity windows for perovskite crystallization in ambient air. Consequently, the optimized 1.68 eV-bandgap n-i-p structured PSC reaches a record-high reverse-scan (RS) PCE of 22.09%. Furthermore, the versatility and applicability of as-proposed self-buffered molecular migration strategy are certified by employing various shielding materials and 1.53 eV-/1.77 eV-bandgap perovskite materials. The n-i-p structured PSCs based on 1.53 eV- and 1.77 eV-bandgap perovskite films achieve outstanding RS PCEs of 25.23% and 19.09%, respectively, both of which are beyond of the state-of-the-art ambient-air processed PSCs. Highlights: 1 A self-buffered molecular migration strategy is developed to suppress spontaneous intermolecular exchange between perovskite intermediate phase and ambient moisture. 2 Exceptionally broad nucleation time and humidity tolerance windows are achieved for perovskite crystallization under ambient air conditions. 1.68 eV-bandgap perovskite solar cells (PSCs) reach a record efficiency of 22.09% when processed in 50–60% relative humidity. 3 The strategy is broadly applicable to 1.53 eV- and 1.77 eV-bandgap perovskite films, enabling high-efficiency PSCs via air-based crystallization processing.